Uganda seed sector profile - Longley, Catherine; Ferris, Shaun; O’Connor, Aline; Maina, Mulemia; Rubyogo, Jean-Claude; Templer, Noel (2021)
This profile focuses on four aspects of the seed sector in Uganda and the interactions between them – the (i) formal seed system, (ii) semi-formal1 or Quality Declared Seed system, (iii) informal seed system, and (iv) emergency seed provisioning. It examines current strategies for seed sector development and makes recommendations for ways in which more integrated, mutually supportive seed systems can be promoted at the broad, sectoral level, to increase smallholder farmers’ access to quality seed of improved varieties.